GdX/UBL4A‐knockout mice resist collagen‐induced arthritis by balancing the population of Th1/Th17 and regulatory T cells. Issue 7 (19th April 2019) - Fu, Yanxia; Liu, Sihan; Wang, Yinyin; Ren, Fangli; Fan, Xuanzi; Liang, Jiao; Liu, Chunxiao; Li, Jun; Ju, Yanfang; Chang, Zhijie
ABSTRACT: Rheumatoid arthritis (RA) is an autoimmune disease associated with synovial hyperplasia and bone and cartilage destruction. T cells, notably T helper (Th )‐1 and Th 17 cells, play a critical role in the pathologic process of RA. However, it remains unclear how Th l and Th 17 cells are regulated during RA. In this study, we report that the small ubiquitin‐like protein X‐linked gene in the G6PD cluster at Xq28 (GdX) regulates the balance of Th 17 and regulatory T (Treg ) cells during collagen‐induced arthritis (CIA). We discovered that the splenocytes of GdX‐knockout (KO) mice were insensitive to T‐cell stimulants. Correspondingly, GdX‐KO mice showed alleviative Th 1‐mediated delayed‐type hypersensitivity and were resistant to CIA compared with wild‐type mice. GdX‐KO mice showed fewer swollen paws, lower serum proinflammatory cytokine and anti‐collagen IgG levels, and decreased synovial hyperplasia. Mechanistically, we observed that deletion of GdX decreased the transcription of proinflammatory cytokines and impaired the Th1 and Th 17 differentiation but increased the Treg cell proliferation. Consistently, deletion of GdX decreased the transcription level of T‐cell‐specific T‐box transcription factor and RAR‐related orphan receptor‐γ transcription factor but increased that of forkhead box P3 after being challenged with type‐II collagen. These findings suggested that GdX functions as an important regulator of Th 1 or Th 17 and Treg cell balance during the inflammatory responses. Therefore, GdX may be a potential target for the therapy of RA.—Fu, Y., Liu, S., Wang, Y., Ren, F., Fan, X., Liang, J., Liu, C, Li, J., Ju, Y., Chang, Z. GdX/UBL4A‐knockout mice resist collagen‐induced arthritis by balancing the population of Th 1/Th 17 and regulatory T cells. FASEB J. 33, 8375–8385 (2019). www.fasebj.org